2014
DOI: 10.5812/ircmj.15765
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Annual Incidence of Abortions in Iran Applying a Network Scale-up Approach

Abstract: Background:Abortions are of major public health concern in developing countries. In settings in which abortion is highly prohibited, the direct interview is not a reliable method to estimate the abortion rate. The indirect estimation methods to measure the rate of abortion might overcome this dilemma; They are practical methods to estimate the size of the hidden group who do not agree to participate in a direct interview.Objectives:The aim of this study was to explore the practicality of an indirect method for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 15 publications
0
29
0
Order By: Relevance
“…Finally, social network-based approaches ask respondents about abortions among their female friends and relatives based on the assumption that women are less likely to under-report others' abortions. [19][20][21][22] We propose the confidante method (approach #5) in which respondents are asked questions about up to three of their closest female confidantes, blending the Best Friend approach 20 and the Anonymous Third Party Reporting 19 to capitalise on the strengths of each. 3 Other approaches to estimating abortion incidence have been proposed, but have yielded inconsistent results.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…Finally, social network-based approaches ask respondents about abortions among their female friends and relatives based on the assumption that women are less likely to under-report others' abortions. [19][20][21][22] We propose the confidante method (approach #5) in which respondents are asked questions about up to three of their closest female confidantes, blending the Best Friend approach 20 and the Anonymous Third Party Reporting 19 to capitalise on the strengths of each. 3 Other approaches to estimating abortion incidence have been proposed, but have yielded inconsistent results.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…In Iran, since 1979, abortion is illegal except in special circumstances, such as when the mother's health is at risk or both the life of the mother and the life of the fetus are at risk. As a result of restrictive abortion laws, around 6000 legal abortions are performed yearly, according to the health ministry reports,20 and illegal abortions are estimated to reach 219 000 (CI 95%, 176 673 to 288 538) 21. In addition, Iran's 2000 Demographic and Health Survey showed that 26% of married women had an abortion in their lifetime and that abortion rates were higher in provinces where contraceptive usage was lower 22.…”
Section: The New Pro-natalist Policy Package: a Critique From A Publimentioning
confidence: 99%
“…Over 10000 ectopic pregnancies are diagnosed each year [4]. In Iran, 13 stillbirths per 1000 live births have been reported [5], but accurate statistics on miscarriage rates in Iran are not available, and from 70.45 to 116.9 miscarriage per 1000 live births are reported [6].…”
Section: Introductionmentioning
confidence: 99%